2000
DOI: 10.1007/s11745-000-0496-z
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and distribution of docosapentaenoic acid (n−6) in rats and rat hepatocytes

Abstract: In this study, a new marine oil that contains 45% docosahexaenoic acid (DHA, 22:6n-3) and 13% docosapentaenoic acid (DPA, 22:5n-6) was administered to rats. The metabolism and distribution of DPA in rats was investigated. In experiment 1, the effects of DHA and n-6 fatty acids (linoleic acid, LA; arachidonic acid, AA; and DPA) on AA contents were investigated in vivo. LA group: LA 25%, DHA 30%; LA-DPA group: LA 15%, DPA 10%, DHA 35%; LA-AA-DPA group: LA 10%, AA 5%, DPA 10%, DHA 35% were administered to rats fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…Retro-conversion of n-6 DPA was also reported in rat hepatocytes 23 . However, the bioconversion profiles of DPAs have not been compared between several human cell lines established from different tissues and blood.…”
Section: Discussionmentioning
confidence: 72%
“…Retro-conversion of n-6 DPA was also reported in rat hepatocytes 23 . However, the bioconversion profiles of DPAs have not been compared between several human cell lines established from different tissues and blood.…”
Section: Discussionmentioning
confidence: 72%
“…This D6D decline did not stop the increase of 20:4n-6 by 22:5n-6, which implies that the conversion of 22:5n-6 to 20:4n-6 did not involve D6D and supports the retroconversion of 22:5n-6 to 20:4n-6 that had been reported in our previous study. 19) Studies on the retroconversion of 22:5n-6 to 20:4n-6 in rat liver have reported that the retroconversion occured with 22:4n-6 as the intermediate, suggesting that retroconversion took place by direct hydrogenation and subsequent -oxidation. 24) It has been well reported that a 20:4n-6 decline would be caused by 22:6n-3 administration in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…19) The testis is an organ that consumes C22 PUFA to transport the sperm into the vesiculae seminalis. 34) At homeostasis, 22:5n-6 as the dominant C22 PUFA in the testis is believed to be involved in the function of sperm transportation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations